(untitled) (Journal of Academic Research, 2026)
This research addresses the classified by priorty Hadith, by presenting its issues, clarifying its realities, and detailing its aspects, while attempting to establish a link between theoretical study and practical application in narration. The study covers the definition of classified by priorty Hadith, its types, its benefits, as well as the grading and number of such hadiths. It then defines Proirty in Hadeth "al-awwaliyah” and explains the conditions for its "valid consideration" along with the expansion that later scholars introduced to it. The research also discusses the reason for the scholars of hadith giving it special attention, includes the takhrij (source tracing) of the hadith, and mentions some of the works written on the subject. It concludes with the author’s own chain of transmission for the hadith, supporting all discussions with citations from scholars, and critically examining their views according to established scholarly principles with fairness and balance. And Allah is the granter of success and the guide to what is correct.